2012
DOI: 10.1080/0161956x.2012.679590
|View full text |Cite
|
Sign up to set email alerts
|

Defining and Assessing Spiritual Health: A Comparative Study Among 13- to 15-Year-Old Pupils Attending Secular Schools, Anglican Schools, and Private Christian Schools in England and Wales

Abstract: This paper argues that the nation's commitment to young people involves proper concern for their physical health, their psychological health, and their spiritual health. In this context the notion of spiritual health is clarified by a critique of John Fisher's model of spiritual health. Fisher developed a relational model of spiritual health, according to which he conceives defines good spiritual health in terms of good an individual's relationship within to four domains: the personal, the communal, the enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Through religious education, the learning atmosphere can be improved by connecting students regardless of their faith [50]. It has been found that receiving religious education provided students with a higher purpose in life and more social support from peers [55]. It can also be a means for teaching religious beliefs and practices which promote support and care for one another.…”
Section: Discussionmentioning
confidence: 99%
“…Through religious education, the learning atmosphere can be improved by connecting students regardless of their faith [50]. It has been found that receiving religious education provided students with a higher purpose in life and more social support from peers [55]. It can also be a means for teaching religious beliefs and practices which promote support and care for one another.…”
Section: Discussionmentioning
confidence: 99%
“…Although the Durham Report (Commission on Religious Education in Schools, 1970) made it clear that Anglican church schools are not in business primarily to promote religion in general or Christianity in particular, some subsequent commentators have tended to suggest that part of the distinctiveness of church schools may include an emphasis on the religious or spiritual aspects of life (see Carey et al., 1998; Lankshear and Hall, 2003). Alongside such theoretical perspectives about the distinctive concern of church schools with religious and spiritual aspects of life, a clear research tradition has developed in England and Wales concerned with monitoring the religion and spirituality of students attending church schools (see Boyle and Francis, 1986; Francis, 1979, 1986, 1987; Francis and Carter, 1980; Francis and Jewell, 1992; Francis and Penny, 2012; Francis et al., 2012; Lankshear, 2005; Swindells et al., 2010).…”
Section: Attitude Toward Christianitymentioning
confidence: 99%
“…A series of recent articles has argued that the students themselves are central to shaping and to determining the prevailing ethos of schools, and that, as a consequence, the assessment of student attitudes may provide an important indicator of school ethos (Francis and Penny, 2012; Francis et al., 2012). Working within this research tradition, the aim of the present article is to report on a new empirical study concerned with monitoring attitudes toward Christianity among students attending Church in Wales primary schools in order to assess the Christian ethos of these schools.…”
Section: Introductionmentioning
confidence: 99%
“…3. 4 Francis et al used the theoretical basis of the 4D model of SH/SWB to develop a 28-item questionnaire that they employed in studies of youth spirituality in the UK [51,52].…”
Section: Feeling Good Livingmentioning
confidence: 99%